(untitled) (Indian Journal of Animal Production and Management, 2024)
A total of 240 goat rearers, selected at random from three animal husbandry divisions of the district, were interviewed by a pretested schedule and required data were collected, analysed and presented in the present study. Majority of respondents (52.50%) marketed the male kids at the age of 3-4 months, followed by 5-6 months (47.50%). Most of the rearers marketed bucks (63.75%) and does (81.25%) at the age of 5-6 years. Majority of respondents (68.75%) sold goats to middle men and disposed them in their villages (85.42%). The body weight of the animals is the main criteria for selling of goats (59.58%) and the goat rearers perceived the enterprise as remunerative (99.58%). The sale price (Rs.) of buck, doe and kid in the study area was 8662.50±198.87, 6022.92±75.63 and 2237.50±27.68, respectively whereas goat meat was sold for 473.96±2.07 per kg. Majority of the goat rearers perceived shrinkage of grazing and browsing area for goats, lack of financial assistance from banks/ government agencies for the purchase of goats, high cost of feed and fodder, lack of scientific knowledge about feeding and management of goats, feed and fodder shortage and lack of willingness of young generation to take up the goat rearing profession as major constraints in the study area.